ANTESEDEN KEPUTUSAN PEMBELIAN DI DEPOT JAMU ANEKA SEHAT KARANGANYAR - JUN RAHMAT AKBAR (JURNAL WIDYA GANECWARA, 2020)
Researchng to find out and nidescribe the analysis of product quality, brand image, and trust buying decision at Depot Jamu Aneka Sehat Karanganyar. Multiplen linear regression is used to process data in research. F test results showed that the variablessof product quality, brand image, and trust isimultaneously and significantly affected buying decision decision at Depot Jamu Aneka Sehat Karanganyar. This is evidenced by the kkresults of the F test that is fcount 26,02 > ftable 2,47 with a significanto value of 0.000 <0.05. Tu test results showed that product quality 0,034 < 0,05 ebrand image 0,012 < 0,05 trust 0,009 < 0,05 positive and significant effect on Depot Jamu Aneka Sehat Karanganyar.